DESIGN OF RESECTION IMPLANT OF CHIN AREA OF MANDIBLE - V.N. Dvornik; S.G. Yas'ko; L.B. Yerys; O.I. Teslenko (Український стоматологічний альманах)
Partial arthroplasty of the lower jaw at the present stage is one of the alternative methods of rehabilitation of patients with tumors or traumatic injury maxillofacial area. Project resection implant automatically using special CAD / CAM software.